Promoting Food Safety in Indonesia's Online Food Delivery Services - Ira Aprilianti; Felippa Amanta (Center for Indonesian Policy Studies (CIPS), 2020)
Indonesia's online food delivery sector is expected to grow by 11.5% annually from 2020 to 2024. Food delivery also opened opportunities for small F&B business owners to sell products. However with the entrance of more vendors, ensuring food safety remains a challenge. This policy paper analyzes food safety challenges in light of the growing online food delivery sector in Indonesia. The paper addresses food safety standards, pre-market certification, and post-market supervision. Through this paper CIPS also calls for regulators to reduce barriers to market entry for micro-small sized enterprises, and incorporate co-regulation approached in the policy making process with the private sector.
Keywords: 330; food safety; online food delivery service; gojek; grab; gofood; grabfood; giz; ira; felippa; plastic ban; bpom; ministry of health; SME; small businesses